ظاهرة الإعراب وموقف علماء العربية قدامى ومحدثين (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يتناول هذا البحث قِدم لغتنا العربية , وعراقتها ,  ثم يبين قِدم ظاهرة الإعراب في اللغات السّامية عامّة, والعربية خاصة , ويتعرض إلى علامات الإعراب , وتطورها , ويُوضح ما إذا كانت نشاطاً أصيلاً في العربية نفسها , أو أنها وليدة التأثر و التأثير من أنماط أخرى من الإعراب في غيرها من اللغات , ويبيّن دور أبي الأسود الدّؤلي , والخليل بن أحمد الفراهيدي في وضع ألقاب الإعراب وعلاماته , ثم يشرح البحث المعنى اللغوي, والاصطلاحي للإعراب , ويعرض مواقف علماء العربية حول علاقة العلامات الإعرابية بالدّلالة , ويقف عند مفهوم الإعراب في نصوص تراثنا النحوي وموقف علماء العربية خاصة سيبويه –المبرد –ابن جني, وعبد القاهر الجرجاني من مفهوم الإعراب , ويجيب البحث عن سؤال : هل يكفي الإعتماد على العلامة الإعرابية وحدها في  تفسير المعاني النحوية؟  وينتهي البحث بإظهار أهمية الإعراب , ومكانته في لغتنا العربية , ثم خاتمة البحث, ونتائجه , وتوصياته . This research tackles the genesis and development of the Arabic language and shows the history of the case phenomenon in the Semitic languages in general and the Arabic language in particular. It tackles case markers and their development to show whether they are an original feature of Arabic itself or they are the result of its interaction with other languages. The paper shows the role of Abu al-Aswad Aduali and al-Khaleel bin Ahmad al-Faraheedi in naming case markers. The research also tries to explain the linguistic as well as the terminological use of case and case markers. It shows the opinion of Arabic grammarians about the relationship between case and meaning with special attention to the concept of case in the literature and the opinion of Arabic grammarian such as Sebaweye, al-Mubared, Ibn Jinni and Abd al-Qaher al Jerjani concerning the concept of case The research question is: Is it enough to depend on case markers alone to interpret the syntactic meaning? In the end the research tries to show the importance of case and its place in Arabic.